Regional Nerve Block Complication Analysis Following Peripheral Nerve Block During Foot and Ankle Surgical Procedures. Issue 4 (22nd October 2020) - Lauf, Jason A.; Huggins, Pearson N.; Al-Issa, Mohammed; Byrne, Brian M.; Large, Bryan; Long, Joseph M.; Whitehead, Brent; Cheney, Nicholas A.; Law, Timothy
Category: Other; Ankle; Ankle Arthritis; Bunion Introduction/Purpose: Foot and ankle surgeries are often be accompanied by a peripheral nerve block as a method of reducing post-operative pain. The major nerve targeted is the popliteal nerve. The nerve can be supplemented with a target of the adductor canal or saphenous nerve. Higher than expected complication rates with peripheral nerve blocks has led to increased concern among both surgeons as well as patients. To our knowledge, no study has been able to identify risk factors that may predispose a patient to one of these complications. Our goal was to attempt to identify those risk factors. Methods: We reviewed patient charts who underwent a foot and ankle procedure between 2014 and 2018 as performed by the senior author. The review yielded 992 procedures performed across four surgical locations. Of these, 137 procedures were removed because no regional block was used. The remaining cases were analyzed for nerve complications, defined as sensory (paresthesia, numbness, tingling, or burning pain) or motor (weakness or paralysis) deficits along the distribution of a peripheral nerve. The patients were divided into blocked patients with and without complications. The groups were evaluated for demographic differences. The categories consisted of age, sex, diabetic status, smoking, previous procedures, previously diagnosed neuropathies, surgical location, body mass index (BMI), race, and insurance provider. Statistical analysis was performed using SAS software. To determine significance of these different factors, Chi-square values were obtained for each data set. Additionally, a regression analysis was performed to identify odds ratio for individual factors. Results: The overall complication rate was 10.1% with a total of 855 blocks given. The significant factors associated with a complication were age (p=0.0061), BMI (p=0.0031), location (p=0.0016), and smoking status (p=0.0026). Factors that were not significantly associated with complications were sex, diabetes status, previous procedures requiring a block, previously diagnosed neuropathies, race, and insurance provider. A regression analysis was performed to determine odds ratio for individual factors. Those with significant higher odds ratio were age between 40-65 years, normal or underweight BMI, surgery occurring at an Outpatient Surgery Center, and current smoker. Conclusion: Current literature has reviewed operative variables such as tourniquet time and epinephrine use, while others have looked at diabetes and age as predictors of nerve block complications. Our study focuses more on epidemiological factors that can predict an increased risk. Our study helped to reinforce the findings previous literature has found in regards to age and diabetes status. This study has also introduced some new factors that can help the surgeon decide if a nerve block is necessary for each surgical patient.